Effect of Ferilizer on the Yield of Maize (Zea mays L.) - Rátonyi, Tamás; Sulyok, Dénes; Huzsvai, László; Megyes, Attila (Acta Agraria Debreceniensis, 2003)
The effect of fertilization on the yield of maize was examined on chernoem soil with lime deposits at the experimental station at Látókép of the Center for Agricultural Sciences, University of Debrecen. The yields of maize were evaluated using quadratic regression function, in three years – between 2000 and 2002 – in non-irrigated and irrigated treatments. After calculating the regression equations, by derivation of the functions, we have determined the amount of fertilizers needed for maximum yield. In the non-irrigated treatments, maximum yield and the active substance amount of fertilizer was as it follows: in 2000, yield of 9,133 t/ha with the application of 384 kg/ha mixed active substance, while in 2002 a yield of 6,289 t/ha with the application 236 kg/ha NPK active substance was achieved. In 2001, due to the favourable precipitation, a yield of 9,864 t/ha was achieved with the application of 245 kg/ha fertilizer. In the case of maximum yield, compared to the unfertilized control, the yield increase was 2,5-5 t/ha. The average increase for 1 kg of NPK fertilizer was 13-19 kg. We also determined the necessary fertilizer dosage for maximum yield in irrigated treatments. In 2000, 10,003 t/ha with a dosage of 423 kg/ha, in 2001, 11,542 t/ha with a dosage of 277 kg/ha and in 2002, 8,596 t/ha of maximum yield could be achieved with a fertilizer treatment of 277 kg/ha in the examined three years. The yield increase, in irrigated treatments, varied between 3,9-5,9 t/ha so it was greater than in the case of non-irrigated experimetal plots. The yield increase for 1 kg fertilizer varied between 12-21 kg.